O23 Identification of protein-quantitative trait loci (pQTLs) in the interferon signalling pathway. (23rd March 2020) - Lundtoft, Christian; Pucholt, Pascal; Sandling, Johanna K; Rönnblom, Lars; Hagberg, Niklas
Abstract : Background: Interferon (IFN)-α and IFN-γ are important cytokines in the pathogenesis of systemic lupus erythematosus (SLE), and several of the genetic associations with SLE are found in genes that are fundamental for the IFN response (e.g. TYK2, STAT4, IRF5 ). This study aimed to define the genetic regulation of the IFN system, and to link disease-associated SNPs to alterations in the IFN system. Methods: Peripheral blood mononuclear cells from 303 healthy individuals were stimulated with IFN-α or IFN-γ (figure 1 ). Basal levels of IFN-receptors (IFNAR2 and IFNGR1) and IFN-induced phosphorylation of STAT1 and STAT4, expression of CXCL9, CXCL10, HLA-ABC and HLA-DRPQ was determined in 6 cell subsets using flow cytometry. Each read-out was mapped as a pQTL using 3.4 million SNPs with a minor allele frequency ≥5% (Illumina Global Screening Array with subsequent genome-wide imputation) in an additive model correcting for covariates. pQTLs were probed for overlap with GWAS SLE-associated SNPs. Results: We identified 8 genome-wide significant pQTLs (p<5.0e-8), 3 of which were associated with basal IFN receptor levels, 3 with IFN-α, and 2 with IFN-γ-induced traits. One pQTL affected protein expression in cis (IFNAR2), whereas the other were trans -pQTLs. The strongest association was observed for a SNP in HLA-A that affected IFNAR2 level in B cells (p=3e-26), CD8 + T cells (3e-12) and CD4 + T cells (p=9e-10). A trans -pQTL for IFNGR1 level in monocytes (rs1801274 in FCGR2A; p=3e-23) and a suggestive significant pQTL (p<5.0e-5) for IFN-γ-induced STAT1 phosphorylation in monocytes (rs912784 in LRRC63) were previously associated with SLE. Notably, none of the SNPs in TYK2, STAT4 or IRF5 reached the suggestive significant levels for the parameters studied, and no enrichment of SLE-associated SNPs were identified among pQTLs. Conclusions: We demonstrate a cell-type and stimuli-specific genetic regulation of the IFN system. Two SNPs previously linked to SLE were associated with alterations in the IFN- γ -receptor expression or response. Further studies to determine the underlying mechanisms of these associations are ongoing.